NILAI PENDIDIKAN ISLAM DALAM RUQYAH SYAR’IYYAH PADA KOMUNITAS RUQYAH SYAR’IYYAH ALHAQ BENGKULU - M Luthfi (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2017)
Abstract: Ruqyah  became a phenomenon. A term  that  is still felt strange  in the  ears  of the  Muslims. This interesting phenomenon coincided with the increasingly  widespread practices of polytheism, especially in the case  of treatment performed by shamans and paranormal. On the other  hand  understanding of the Muslims will ruqyah very least, can be said to hear  his name alone  can be said recently.  From where the need for the public  to understand the  importance Ruqyah  Syar’iyyah as exemplified by the  Prophet in order  not  to get stuck with a variety of treatments that appear un-Islamic but essentially  idolatry. Community presence Ruqyah Syar’iyyah Alhaq Bengkulu  (RSAB) seeks to provide  solutions  to the problems. From some keyataan above, formulated the problems include:  educational values of Islam in Ruqyah Syar’iyyah in Community RSAB and how  peruqyah spiritual  experiences during  the  run  ruqyah  therapy  in Community  RuqyahSyar’iyyahAlhaq Bengkulu. The research objective was to determine the values of Islamic education in Ruqyah Syar’iyah. While the benefits  of the research itself as an input to fortify the people not to get caught  various shamanic practices and  treatment of polytheism. Results  of research and  analysis  of the  data  and  conclusions found  that  the values  of Islamic  education in the  Community syar’iyyah ruqyah  Ruqyah  Syar’iyyahAlhaq Bengkulu  include Value Faith, Values Tauhid, Moral Values, Tolerance Values, Values Honesty, Value Ikhlas, resignation Values, Values constancy and Values Faredah. With ruqyah can help a lot of people that is working to find a cure and completeness of the problem through the Quran and prayers. Treatment with ruqyah is necessary for Muslims to avoid the various treatment idolatry.